Comparative effectiveness of pressurized metered-dose inhaler (pMDI) and dry-powdered inhaler (DPI) salmeterol/fluticasone on chronic obstructive pulmonary disease, a single-center study in Hangdong Hospital - Mongkolrat, Sira (Journal of Nakornping Hospital, 2025)
Background: Chronic Obstructive Pulmonary Disease (COPD) is a major public health concern in Thailand. Standard treatment regimens typically include combinations of inhaled corticosteroids with long-acting beta-adrenergic agonists (ICS/LABA) or long-acting muscarinic antagonists (LAMA). Given the financial constraints of the Universal Coverage Program, evaluating both the clinical efficacy and cost-effectiveness of available therapies is essential. This study aimed to compare the effectiveness and cost of Salmeterol/Fluticasone administered via pressurized metered-dose inhaler (pMDI) versus dry powder inhaler (DPI), and to identify risk factors associated with exacerbations and clinical outcomes. Materials and Methods: This retrospective cohort study included all COPD patients who regularly visited Hangdong Hospital and received ICS/LABA therapy between January and December 2023. Demographic data, treatment details, and clinical outcomes were reviewed and analyzed. Descriptive statistics were applied, and risk factors were identified using logistic regression. Variables with p < 0.1 in univariate analysis were included in multivariable models, with results reported as adjusted odds ratios and 95% confidence intervals. Results: Of the 326 patients included, 215 used pMDIs and 111 used DPIs. The DPI group was significantly younger and had a higher proportion of GOLD stage E patients (34.2% vs. 18.6%). Moderate exacerbations were more frequent in the DPI group, primarily due to greater disease severity, while severe exacerbation rates were similar between groups. The strongest predictors of severe exacerbations were a history of more than one prior exacerbation (Adjusted OR 6.70, 95% CI 1.17–38.32, p = 0.033) and LAMA use (Adjusted OR 4.71, 95% CI 2.08–10.70, p < 0.001). Outpatient costs were significantly higher for DPI users, whereas inpatient costs were higher for pMDI users, partly due to increased rates of respiratory failure (25.6% vs. 8.8%, p = 0.018) and mortality (14.6% vs. 0%, p < 0.001). Conclusion: Neither inhaler type was independently associated with an increased risk of exacerbation. Key risk factors for severe exacerbations included a history of multiple prior exacerbations and LAMA use. DPI use was associated with fewer severe complications and resulted in 13% lower total healthcare costs compared to pMDI use.